Swimming-induced pulmonary oedema in two triathletes: a novel pathophysiological explanation. (November 2014) - Casey, Helen; Dastidar, Amardeep Ghosh; MacIver, David
Lesson: Swimming-induced pulmonary oedema/edema (SIPO/SIPE) is likely to become commoner with increasing popularity of endurance sports meaning an increased awareness by participants, organisers and medical personnel is important, especially as individuals are at increased risk of future life threatening episodes and drowning if an accurate diagnosis and appropriate advice are not given. The most important risk factors we identified are a highly trained individual, competitive exercise, hypertension and cold environment.